2006
DOI: 10.1042/bj20051643
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the α subunit of translation initiation factor-2 by PKR mediates protein synthesis inhibition in the mouse brain during status epilepticus

Abstract: In response to different cellular stresses, a family of protein kinases phosphorylates eIF2alpha (alpha subunit of eukaryotic initiation factor-2), contributing to regulation of both general and genespecific translation proposed to alleviate cellular injury or alternatively induce apoptosis. Recently, we reported eIF2alpha(P) (phosphorylated eIF2alpha) in the brain during SE (status epilepticus) induced by pilocarpine in mice, an animal model of TLE (temporal lobe epilepsy) [Carnevalli, Pereira, Longo, Jaqueta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Translation was not assessed in our conditions limiting discussion on the pathophysiological significance of our observations. It is indeed possible that protein expression does not entirely match mRNA synthesis as seizures are reported to depress protein synthesis (Wasterlain, 1974;Carnevalli et al, 2006). As an illustration of such a phenomenon, it was demonstrated that, early in the course of soman intoxication, an increase in hsp70 gene transcription was not followed by translation in the protein HSP72 (Baille Le Crom et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…Translation was not assessed in our conditions limiting discussion on the pathophysiological significance of our observations. It is indeed possible that protein expression does not entirely match mRNA synthesis as seizures are reported to depress protein synthesis (Wasterlain, 1974;Carnevalli et al, 2006). As an illustration of such a phenomenon, it was demonstrated that, early in the course of soman intoxication, an increase in hsp70 gene transcription was not followed by translation in the protein HSP72 (Baille Le Crom et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…For example, during ischemia and reperfusion, which often is associated with deficient LTM, there are long-lasting decreases in protein synthesis and increased phosphorylation of eIF2a (DeGracia et al 2002). In addition, increased eIF2a phosphoryation in the brain is associated with epilepsy (Carnevalli et al 2006) and neuronal culture models of Parkinson's disease (PD) (Holtz and O'Malley 2003). Moreover, eIF2a phosphorylation increases in the hippocampus of mouse models of Alzheimer's disease (Page et al 2006;Kim et al 2007), as well as brains of AD patients (Kim et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hyperphosphorylation of 4E-BP1, releases eIF4E, thus increasing cap-dependent translation initiation. Stress conditions (e.g., nutrient limitation) have been associated with the phosphorylation of eIF2 (4,48) and the dephosphorylation of 4E-BP1, which would lead to a reduction in protein synthesis (19,24,31). It isunknown, however, whether/how the molecular control of protein synthesis would respond in different tissues when exposed to the same milieu.…”
mentioning
confidence: 95%